Combining Survival and Toxicity Effect Sizes from Clinical Trials: NCCTG 89-20-52 (Alliance) - Major-Elechi, Brittny T.; Novotny, Paul J.; Singh, Jasvinder A.; Bonner, James A.; Dueck, Amylou C.; Sargent, Daniel J.; Grothey, Axel; Sloan, Jeff A. (International Journal of Statistics in Medical Research, 2018)
Background: How can a clinician and patient incorporate survival and toxicity information into a single expression of comparative treatment benefit? Sloan et al. recently extended the ½ standard deviation concept for judging the clinical importance of findings from clinical trials to survival and tumor response endpoints. A new method using this approach to combine survival and toxicity effect sizes from clinical trials into a quality-adjusted effect size is presented. Methods: The quality-adjusted survival effect size (QASES) is calculated as survival effect size (ESS) minus the calibrated toxicity effect sizes (EST) (QASES=ESS-EST). This combined effect size can be weighted to adjust for the relative emphasis placed by the patient on survival and toxicity effects. Results: As an example, consider clinical trial NCCTG 89-20-52 which randomized patients to once-daily thoracic radiotherapy (ODTRT) versus twice-daily treatment of thoracic radiotherapy (TDRT) for the treatment of lung cancer. The ODTRT vs. TDRT arms had median survival time of 22 vs. 20 months (p=0.49) and toxicity rate of 39% vs. 54%, (p<0.05). The QASES of 0.18 standard deviations translates to a quality-adjusted survival difference of 5.7 months advantage for the ODRT arm over the TDRT treatment arm (22(16.3) months), p<0.05). Similar results are presented for the four possible case combinations of significant/non-significant survival and toxicity benefits using completed clinical trials. Conclusions: We used a novel approach to re-analyze clinical trial data to produce a single estimate for each treatment that combines survival and toxicity data. The QASES approach is an intuitive and mathematically simple yet robust approach.